Pseudo-inverse simulation of pull-up maneuvers at low and high speeds by means of optimization - Thiemeier, J.; Montemari, F.; Fresta, F.; Litterst, L.; Spiess, C. (My University, 2022)
In the course of the certification process of a helicopter, applying EASA certification specifications and means of compliance, a loads survey is required which is then used for the design process or the stresses verification. Reasonable load cases can be derived from typical maneuvers, e.g. pull-ups, characterized by a phase of positive pitch rate and increased load factor. The paper at hand presents how an optimization of pull-up maneuvers simulated with the flight mechanics code Flightlab can be utilized to acquire desired load cases. The maneuvers are “flown” by prescribing control inputs for longitudinal cyclic and collective, whereas lateral cyclic and pedal a handled by a control system. The simplified input signals for longitudinal and collective controls are parameterized and then altered by an optimization framework, called Maneuver Optimization Tool (MOPT) and written in Python, in order to achieve given maneuver characteristics, e.g. a target pitch rate and main rotor torque. The simulation framework, consisting of Flightlab and the mentioned Python optimization, is introduced, and results are shown for low-speed flight at vl = 70 kts indicated and at never-exceed speed vNE. In addition, four different combinations of low/high helicopter mass, and front/aft center of gravity location are considered.